Inhibition of PbGP43 Expression May Suggest that gp43 is a Virulence Factor in Paracoccidioides brasiliensis (2013)
ABSTARCT: Glycoprotein gp43 is an immunodominant diagnostic antigen for paracoccidioidomycosis caused by Paracoccidioides brasiliensis. It is abundantly secreted in isolates such as Pb339. It is structurally related to beta-1,3-exoglucanases, however inactive. Its function in fungal biology is unknown, but it elicits humoral, innate and protective cellular immune responses; it binds to extracellular matrix-associated proteins. In this study we applied an antisense RNA (aRNA) technology and Agrobacterium tumefaciens-mediated transformation to generate mitotically stable PbGP43 mutants (PbGP43 aRNA) derived from wild type Pb339 to study its role in P. brasiliensis biology and during infection. Control PbEV was transformed with empty vector. Growth curve, cell vitality and morphology of PbGP43 aRNA mutants were indistinguishable from those of controls. PbGP43 expression was reduced 80-85% in mutants 1 and 2, as determined by real time PCR, correlating with a massive decrease in gp43 expression. This was shown by immunoblotting of culture supernatants revealed with anti-gp43 mouse monoclonal and rabbit polyclonal antibodies, and also by affinity-ligand assays of extracellular molecules with laminin and fibronectin. In vitro, there was significantly increased TNF-α production and reduced yeast recovery when PbGP43 aRNA1 was exposed to IFN-γ-stimulated macrophages, suggesting reduced binding/uptake and/or increased killing. In vivo, fungal burden in lungs of BALB/c mice infected with silenced mutant was negligible and associated with decreased lung ΙΛ-10 and IL-6. Therefore, our results correlated low gp43 expression with lower pathogenicity in mice, but that will be definitely proven when PbGP43 knockouts become available. T